Perception of Farmers and Kisan Call Centre Professionals towards Kisan Call Centre services in Agriculture: A Case of Guntur District, Andhra Pradesh, India - G. S. Mahra , V. P. Sharma , S. M. Raut, (Indian Journal of Extension Education, 2015)
Kisan Call Centre (KCC) is one of the most successful and innovative efforts in utilising Mobile based ICT's in rural areas.After its nationwide launch by Department of Agriculture and Cooperation, Ministry of Agriculture, G.O.I in the year2004, it has effectively reduced the gap between farmer and farm information by narrowing the mobility constraints oftechnical staff of various agricultural organisations. The present study has been done to assess the impact andeffectiveness of KCC services and to identify the problems of farmers regarding services of KCC. This study has alsoanalyzed the existing perceptions of farmers and agricultural graduates working at level I in KCC about KCC services.Level of knowledge gained by farmers on package of practices has been analyzed to show the effectiveness of KCCservices.